2020
DOI: 10.1136/bmjoq-2020-000930
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac arrest in the paediatric intensive care unit: defining the problem and developing solutions

Abstract: Thousands of children experience a cardiac arrest event in the hospital each year, with more than half of these patients not surviving to hospital discharge. Cardiopulmonary resuscitation (CPR) depth, rate, velocity and percentage of high-quality chest compressions are modifiable factors associated with improved survival. Therefore, we created a novel and standardised process to track and analyse cardiac arrests in the Duke paediatric intensive care unit (PICU). Our aim was to identify areas for improved Ameri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…In addition, compared with Zeng's report, the current rate of ROSC was slightly lower, while the rate of survival in 24 h post-CPR and survival to discharge were apparently higher (47.3 and 37.4% vs. 35.06 and 28.2%, respectively), implying that the subsequent therapy contributed to the improvement of prognosis. In recently published international reports, the ROSC ratio varied widely from 64.5 to 78% ( 2 , 3 , 11 ), and the survival to discharge rate ranged from 45 to 63% ( 1 , 4 , 7 ), which were better than the results in this study. Thus, more studies on repeated high-quality CPR training, primary disease therapy, and effective advanced life support should be performed to narrow the gap.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In addition, compared with Zeng's report, the current rate of ROSC was slightly lower, while the rate of survival in 24 h post-CPR and survival to discharge were apparently higher (47.3 and 37.4% vs. 35.06 and 28.2%, respectively), implying that the subsequent therapy contributed to the improvement of prognosis. In recently published international reports, the ROSC ratio varied widely from 64.5 to 78% ( 2 , 3 , 11 ), and the survival to discharge rate ranged from 45 to 63% ( 1 , 4 , 7 ), which were better than the results in this study. Thus, more studies on repeated high-quality CPR training, primary disease therapy, and effective advanced life support should be performed to narrow the gap.…”
Section: Discussioncontrasting
confidence: 74%
“…This study is the only multicenter survey of CPA and CPR in PICU based on the Utstein style across China in the past 10 years. Reports in the recent 5 years have declared that the incidence of CPA in critically ill children in the hospital has decreased from 2 to 6% ( 8 , 9 ) to 2.2–5.5% ( 1 , 3 , 4 , 7 , 10 ). In this study, the incidence of CPA in PICU was 3.2%, similar to that observed in the previous studies ( 7 , 11 ) but was lower than the 5.5% in Zeng's report ( 9 ), another multicenter survey in Beijing in 2013.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C-CHEWS is normally done every 4 hours per McLellan et al ( 5 ), but since PCICU is a high dependency unit, we collected C-CHEWS and IDO 2 scores every 2 hours, starting immediately after extubating and continued till discharge/transfer from PCICU. If a patient’s C-CHEWS scores were in yellow ( 3 , 4 ) or red (≥5), the frequency of C-CHEWS and IDO 2 was increased to once every hour. Adverse events were defined as a need for reintubation, cardiopulmonary resuscitation (CPR), or death.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, CA is associated with significant morbidity due to ischemic brain injury and poor neurological outcomes ( 3 ). Studies have shown an increase in survival to discharge rate by up to 16% by implementing educational and community-based initiatives to improve recognition of early signs of CA ( 4 ). This lays special emphasis on the importance of early recognition of such adverse events to improve morbidity and mortality rates associated with CA.…”
mentioning
confidence: 99%